Implementasi Azure Cognitive Services dalam Pengembangan Chatbot Layanan Informasi Skripsi - Nur Asiah Ramdani; Asriyanik Asriyanik; Winda Apriandari (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
The Thesis is a compulsory subject that must be followed by undergraduate students to complete their study period. The Thesis is different from other courses related to the procedures in it. In the Informatics Engineering study program at Muhammadiyah University of Sukabumi, the dissemination of thesis information was spread through 5 different media, but this was not effective because it took a lot of time and made the work repeated. Therefore, to facilitate the dissemination of information, the researchers created a chatbot application that can answer questions about thesis information automatically without human supervision. To produce a smart chatbot, Microsoft Azure Cognitive Services QnA Maker service is used in its manufacture. The chatbots were tested using alpha and beta testing and concluded that making chatbot applications with Azure Cognitive Services QnA Maker made finding thesis information more accurate, effective, and efficient.